Photocatalytic degradation kinetics of Orange G dye over ZnO and Ag/ZnO thin film catalysts - Tekin, Derya; Tekin, Taner; Kiziltas, Hakan (Scientific reports, 2019)
The degradation of water pollutants with photocatalysts is one of the most studied subjects in the past 20 years. Although considerable studies have been completed in this field, kinetic model studies are still a major inadequacy. In this study, ZnO and Ag/ZnO thin film photocatalysts were synthesized and SEM-EDS, XRD and chronoamperometric measurements were used the characterization of photocatalysts. The network kinetic model was applied the photocatalytic degradation of Orange G using ZnO and Ag/ZnO thin film photocatalysts. The photocatalytic degradation of Orange G was investigated under the different reaction medium (initial dye concentrations, temperature, light intensity). It was found that the network kinetic model is the most appropriate model for the degradation of Orange G dye on the ZnO and Ag/ZnO thin film photocatalysts. The calculated adsorption equilibrium (K B ) constant and activation energy of ZnO thin film photocatalyst are 0.0191 and 21.76 kj/mol, respectively. Additionally, the calculated values for Ag/ZnO thin film photocatalyst are 0.035 and 18.32 kj/mol. The general rate equations were determined for each photocatalysts.